The use of Zuckerkandl's tubercle as an anatomical landmark in identifying recurrent laryngeal nerve and superior parathyroid gland during total thyroidectomy: a prospective single-surgeon study - Gurluler, Ercument (Frontiers in Surgery, 2023)
Objective: To determine the incidence and characteristics of Zuckerkandl's tubercle (ZT), and its relationship with recurrent laryngeal nerve (RLN) and the superior parathyroid gland (SPG) in the setting of total thyroidectomy. Methods: A total of 421 patients (mean (min-max) age: 45.6 (18-78) years, 76.2% were females) who had total thyroidectomy were included in this prospective single-surgeon thyroidectomy series study. Patient demographics and thyroidectomy indications (benign and malignant) were recorded in each patient. The presence, grade and laterality of ZT, and its relationship with RLN and SPG were recorded during surgery.Results: Most of the thyroidectomy indications (69.1%) were related to a malignant disease. The ZT was unrecognizable in 41(9.7%) of 421 patients. In 380 patients with identifiable ZT, the grade 2 (46.3%) ZT was the most common finding. Majority of ZTs (92.9%) were unilaterally located (rightsided: 64.9%; left-sided: 35.1%). In majority of the cases (83.2%), the RLN was found to lie medial to ZT. Overall, SPG was identified in close proximity to ZT in 66.6% of patients (Class 2 [0.5-1 cm from ZT] in 46.6% and Class 3 [<0.5 cm from ZT] in 20.0%). SPG was more likely to be identified in close proximity to ZT when the grade of ZT was higher, which was found to be located 0.5-1 cm from the ZT in 56.9% and 42.7% of grade 2 and grade 3 ZTs, respectively, and <0.5 cm from the ZT in 46.1% of grade 3 ZTs.In conclusion, this prospective single-surgeon thyroidectomy series study indicates the likelihood of localizing the RLN medial to ZT, and the SPG in close proximity to ZT during total thyroidectomy operations. Hence, the ZT can be used as a reliable and constant landmark to localize both the RLN and the SPG during thyroid surgery, which enables minimizing the risk of iatrogenic injury to RLN, while ensuring a parathyroid-sparing thyroidectomy. The thyroid surgeon should have complete knowledge of thyroid gland anatomy and embryogenesis and should follow a careful and meticulous approach particularly for dissections around larger ZTs, given the increased likelihood of SPG and RLN to be in close proximity.